The Effectiveness of Group Guidance with Simulation Game Techniques to Improve Student Assertive Behavior (Jurnal Bimbingan Konseling, 2019)
The purpose of this study is to know the effectiveness of group guidance with simulation games techniques to improve student assertive behavior of Vocational High School students. This research method is an experiment using the design of one group pre-test – post-test involving 10 students who have low assertive behavior as group members. The results of this study indicate an increase in assertive behavior students before being given the game simulation technique of 84.40 (SD = 14.05) to 148.50 (SD = 8.57; t(10) = 12.29, p < 0.01). This study confirms that group guidance with simulation game techniques can be applied to improve student assertive behavior.